PUBLIC HEARINGS (Revista Paradigma, 2025)
This article aims to analyze the institution of the public hearing within the Executive, Legislative, and Judicial branches, from the perspective of rights of personality and democratic theory. Public hearings are considered, beyond being a procedural formality, a fundamental mechanism of social participation that enables active democracy and increases the legitimacy of state decisions. The article focuses especially on the application of public hearings in the Judiciary and their importance for the protection of rights of personality, also assessing whether they are effective instruments to ensure the realization of rights related to human dignity. To address these issues, the article adopts a qualitative approach through a literature review of books, articles, and national and international documents on the subject. In conclusion, it is argued that public hearings, when guided by criteria of inclusion, plurality, and recognition, represent an essential constitutional practice for strengthening democratic dialogue and ensuring the protection of rights of personality in the Brazilian context.
Keywords: Public hearing. Participatory democracy. Personality rights. Enforcement of rights. Popular participation.